2017
DOI: 10.1007/s12105-017-0852-8
|View full text |Cite
|
Sign up to set email alerts
|

Sialadenoma Papilliferum: Analysis of Seven New Cases and Review of the Literature

Abstract: Sialadenoma papilliferum (SP) is a rare benign salivary gland neoplasm that comprises from 0.4 to 1.2% of all salivary gland tumors. The tumor is so named because of its microscopic resemblance to the syringocystadenoma papilliferum, an uncommon benign tumor of sweat gland origin. The purpose of this paper is to report the clinical and microscopic features of seven new cases of SP and combine them with cases previously reported in the English language literature to further define this unusual lesion. Combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 40 publications
(32 reference statements)
1
58
0
Order By: Relevance
“…The histological origin and tumorigenesis of SP have been long debated and remain to be elucidated . In earlier descriptions the possibility of a metaplastic or reactive process was suggested .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histological origin and tumorigenesis of SP have been long debated and remain to be elucidated . In earlier descriptions the possibility of a metaplastic or reactive process was suggested .…”
Section: Discussionmentioning
confidence: 99%
“…performed a retrospective search to identify institutional and consultation cases with an initial diagnosis of ‘SP’, ‘intraductal papilloma’, ‘cystadenoma’, ‘cystadenocarcinoma’, or miscellaneous papillary–cystic tumour of the minor salivary glands, and retrieved a total of 28 cases. Histological diagnoses were made on the basis of the 2017 World Health Organization (WHO) classification of head and neck tumours and related previous studies . After re‐evaluation, the cases were reclassified as follows: SP ( n = 10), SP‐like intraductal papillary tumour (SP‐IPT) ( n = 2), IPMN ( n = 9), intraductal papilloma ( n = 2), cystadenoma ( n = 3), and cystadenocarcinoma ( n = 2).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, sialadenoma papilliferum is characterized by a combination of exophytic projection of the surface squamous epithelium and inward papillary proliferation of duct epithelial cells [ 1 , 2 , 6 , 7 ]. The underlying glandular component forms papillary extensions surfaced by columnar or cuboidal cells or both, which is contiguous with underlying arborizing ductal structures and cystic spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of cases occur in the palate (particularly the hard palate), others in decreasing order in the buccal mucosa, upper lip, retromolar pad, and parotid gland, but cases have also been reported in the bronchus and nasopharynx [53,54]. The peak age is in the 6th decade [55]. SP was first described by Abrams and Finck in 1969 [56] and presents clinically as a painless exophytic papillary mass, often misinterpreted clinically as squamous cell papilloma, warty dyskeratoma or verrucous carcinoma [57].…”
Section: Sialadenoma Papilliferummentioning
confidence: 99%
“…SP was first described by Abrams and Finck in 1969 [56] and presents clinically as a painless exophytic papillary mass, often misinterpreted clinically as squamous cell papilloma, warty dyskeratoma or verrucous carcinoma [57]. A literature review in 2007 by Mahajan et al [58] found a total of only 47 reported cases, a number that has increased substantially following the 7 new cases reported by 2018 [55].…”
Section: Sialadenoma Papilliferummentioning
confidence: 99%